LEGAL ASPECTS OF MIGRANTS SMUGGLING AT THE SEA BORDER BETWEEN HELLAS AND TURKEY - Korontzis Tryfon (European Scientific Journal, ESJ, 2014)
Organized crime (Note 1) has a global character and is one of the most serious threats in the modern societies for decades. This phenomenon because of the characteristics that govern modern societies and economies, namely globalization, transnational flows, reduction of distances due to the technology evolution has taken international dimensions. These evolutions help the development of international profitable illegal activities. Organized Criminal Groups (OCG) are operating simultaneously in more than one countries internationalizing with that way crime, making difficult and painful its effective and comprehensive combat. Besides the international character of modern organized crime, an additional problem is the modernization of mode and methods of action that are used by criminal groups. In criminal phenomena that characterize our time is included illegal immigration. Illegal immigration is a social – political, and economic phenomenon that leads people to search a better quality of living in various places different of their origin place. Consequently the hope of these people was and is a profitable business for others.